METABOLIC ACTIVITY OF MICROFLORA AND DIET CORRECTION OF INTESTINAL MICRO BIOCENOSIS IN INFANTS WITH ENTEROCOLITIS - E.R. Meskina (Вопросы современной педиатрии)
The study of effectiveness of prebiotic dose of lactulose in 200–400 ml of milk formula «Bifidus» in nutrition of infants, hospitalized with infectious enterocolitis, was performed. Microbiological effectiveness of «Bifidus» was estimated in 1–1,5 months according to the results of gas-fluid chromatography with evaluation of short-chain fatty acids (SCFA). Statistically significant increase of initially low level of SCFA testified to the restoration of quantity and activity of microbe populations in colon. The dynamics of SCFA in some rates was similar to that ones in children, receiving breast feeding and with data on quality-quantity bacteriological analysis. The study showed the key role of butyric acid level that influences on several microbiological features of intestinal flora in acute stage of infectious enterocolitis. Key words: infants, infectious enterocolitis, intestinal flora, short-chain fatty acids, lactulose.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(1):44-51)